Pengaruh Struktur Organisasi Dan Kepuasan Kerja Terhadap Produktivitas Karyawan PT. Insuindomas Putra Medan - Lambok Sihite; Sari Wulandari (LPPM Universitas Labuhanbatu, 2022)
this study aims to analyze the effect of organizational structure and job satisfaction on employee productivity PT. Insuindomas Son Of Medan.The method used in this study is quantitative. Sampling technique in this study is saturated sampling as many as 60 employees. Data collection methods using questionnaires/questionnaires. The results of multiple regression analysis obtained a constant value (A) of 1.475,B1 of 0.367 and b2 of 0.312 to obtain multiple linear regression equation Y = 1.475 + 0,367x1 + 0, 312x2 + e. The results obtained from the value of the coefficient of 0.326, where the value of t-count > t-table (3.442> 1.6706) and significant of 0.001 smaller than 0.05 means that the organizational structure has a significant effect on employee productivity, then H1 is accepted. The value obtained from the value of the coefficient of 0.562, where the value of t-count < t-table (5.892> 1.6706) and significant of 0.000 smaller than 0.05 means that job satisfaction has a significant effect on employee productivity, then H2 is accepted. Obtained value Fhitung (30.625) > Ftable (3.16), and the significance value of 0.000 < 0.05 then it can be concluded the third hypothesis is accepted, meaning the variable organizational structure (X1) job satisfaction (X2) affect simultaneously (simultaneous) to employee productivity variable (Y). The value of the coefficient of determination that has been adjusted (R Square) of 0.518 this means that 51.8% of the dependent variable can be explained by the independent variable while the remaining 48.2% is explained by other variables outside the variables studied.